PENGARUH TRANSPORTASI HALAL, PENGADAAN HALAL, DAN MANUFAKTUR HALAL TERHADAP KEUNGGULAN OPERASIONAL BERKELANJUTAN YANG DIMODERASI OLEH STRATEGI MITIGASI RISIKO PANDEMI - Hadi Hidayat; Wahyuningsih Santosa; Ratna Darasih; Dorina Widowati (Universitas Sarjanawiyata Tamansiswa, 2026)
This study analyzes the influence of halal transportation, halal procurement, and halal manufacturing on sustainable operational excellence (SOE) in the halal cosmetics industry at PT Paragon Technology and Innovation, moderated by SARS-CoV-2 pandemic risk mitigation strategies. It examines how halal supply chain practices enhance operational efficiency, consistency, and sustainability amid mandatory halal certification and global market dynamics. Employing an explanatory quantitative cross-sectional design, the study surveyed 227 employees from the company's halal supply chain divisions via purposive sampling and a 5-point Likert scale questionnaire. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS), including outer/inner model evaluations, product indicator moderation tests, and bootstrapping at α=5%. Findings reveal significant positive effects of halal transportation (H1: t=3.45>1.96), halal procurement (H2: t=4.12>1.96), and halal manufacturing (H3: t=5.23>1.96) on SOE (R²=0.520), while pandemic mitigation does not moderate these relationships (H4-H6 insignificant). These results underscore halal practices' role in driving SOE for Indonesia's halal cosmetics sector.